2010
DOI: 10.4236/jwarp.2010.22015
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Action and Physicochemical Properties of Stabilized Silver and Gold Nanostructures on the Surface of Disperse Silica

Abstract: This work is devoted to the synthesis and stabilization of nanosized Ag/SiO 2 and Au/SiO 2 disperse materials and investigation their morphology, optical and antimicrobial properties. First, Ag and Au nanoparticles (NPs) were produced in colloids via chemical (Ag) or photochemical (Au) reduction of appropriate ions. To prevent the oxidation of Ag NPs in colloid solution, external binary stabilizing agents PVP and SDS were used. Then, Ag and Au NPs (0.01-0.05% wt) were adsorbed from their colloid solutions on h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…We showed that the biocidal characteristics of gold nanoparticles show up well when they are used at the growth stage of E. coli, while silver nanoparticles are effective during the elimination of already grown colonies [123][124][125]. The effectiveness of the nanoparticles can be intensified by depositing them on a support with a highly developed surface.…”
Section: Bactericidal Characteristics Of Stabilized Silver Nanostructmentioning
confidence: 99%
See 2 more Smart Citations
“…We showed that the biocidal characteristics of gold nanoparticles show up well when they are used at the growth stage of E. coli, while silver nanoparticles are effective during the elimination of already grown colonies [123][124][125]. The effectiveness of the nanoparticles can be intensified by depositing them on a support with a highly developed surface.…”
Section: Bactericidal Characteristics Of Stabilized Silver Nanostructmentioning
confidence: 99%
“…The Ag nanoparticles obtained during the high-temperature solvolysis of an ethanol solution of AgNO 3 in the presence of dodecanethiol also remain stable after drying [25]. The principle of the stabilization of Ag nanoparticles with polymers or surfactants was applied successfully to the synthesis of composite systems based on highly dispersed silica (HDS) containing stable nanoparticles of silver with PVP and/or SDS as stabilizers [124,125].…”
Section: Stabilization Of Silver Nanoparticles On the Surface Of Dispmentioning
confidence: 99%
See 1 more Smart Citation
“…The antibacterial properties of gold NPs (Au-NPs) have also been evaluated. In one study, Au-NPs with a size of 20 to 30 nm showed no antibacterial effect on S. aureus ATCC 6538 and E. coli K-12 NCTC 10538 (64). The MIC of Au-NPs against S. aureus was also shown to be significantly higher than that of Ag-NPs (65).…”
Section: Nanoparticlesmentioning
confidence: 99%
“…Although the exact mechanism of antibacterial effect of gold nanoparticles is not fully understood but it is assumed that Au NPs binds to the cell wall of the bacterium and suppressed bacterial growth at the rst stage of their reproduction. 64 Due to their well-developed surface chemistry and the smaller size, gold nanoparticles can interact with the microorganisms with ease and cause destructive effects on them. 65 SiO 2 @Ag nanoparticles showed better antibacterial effects than the SiO 2 @Au nanoparticles and were able to hinder the growth of both bacterial species.…”
Section: Antimicrobial Activity Of Sio2@au-ag Ncsmentioning
confidence: 99%